Implementation of Varied Learning and Parental Collaboration in Improving the Quality of Learning - Nurul Lailatul Fitriah; Siti Nurhasanah; Tulai Hahning Safitri; Nur Azizah (STAI Serdang Lubuk Pakam, 2026)
Islamic Religious Education plays a crucial role in shaping students’ character, morals, and spirituality, making effective teaching strategies essential. However, current teaching practices are still characterized by monotonous methods and limited parental involvement. This study aims to analyze the implementation of varied teaching methods and parental collaboration in improving the quality of education at SD IT Al-Izhar Pekanbaru. The study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving teachers, the principal, and parents via purposive sampling. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, while triangulation was used to ensure data validity. The findings indicate that varied learning through group discussions, educational games, and project-based learning can enhance student engagement and understanding. Parent-school collaboration was carried out through intensive communication, parenting programs, and home learning support. These strategies had a positive impact on students’ motivation, participation, and learning outcomes. Overall, the integration of varied learning approaches and active parent collaboration effectively improved the quality of learning.